Two-colour chewing gum mixing ability test for evaluating masticatory performance in children with mixed dentition: validity and reliability study - AKYÜZ, SERAP HATİCE (WILEY, 2017)
The unappealing taste of the chewing material and the time-consuming repetitive task in masticatory performance tests using artificial foodstuff may discourage children from performing natural chewing movements. Therefore, the aim was to determine the validity and reliability of a two-colour chewing gum mixing ability test for masticatory performance (MP) assessment in mixed dentition children. Masticatory performance was tested in two groups: systemically healthy fully dentate young adults and children in mixed dentition. Median particle size was assessed using a comminution test, and a two-colour chewing gum mixing ability test was applied for MP analysis. Validity was tested with Pearson correlation, and reliability was tested with intra-class correlation coefficient, Pearson correlation and Bland-Altman plots. Both comminution and two-colour chewing gum mixing ability tests revealed statistically significant MP differences between children (n = 25) and adults (n = 27, both P < 0.01). Pearson correlation between comminution and two-colour chewing gum mixing ability tests was positive and significant (r = 0.418, P = 0.002). Correlations for interobserver reliability and test-retest values were significant (r = 0.990, P = 0.0001 and r = 0.995, P = 0.0001). Although both methods could discriminate MP differences, the comminution test detected these differences generally in a wider range compared to two-colour chewing gum mixing ability test. However, considering the high reliability of the results, the two-colour chewing gum mixing ability test can be used to assess masticatory performance in children, especially at non-clinical settings.
Keywords: mastication; validity; reliability; chewing gum; children; mixed dentition; OCCLUSAL CONTACT; FORCE; MALOCCLUSION; EFFICIENCY